Seguimiento A Las Recomendaciones Generales En La Auditoría A Los Procesos Del Área De Recaudación Y Cartera Del CNEL EP - Rosado Alava, Victoria Graciela (2018)
The present investigation entitled FOLLOW-UP TO RECOMMENDATIONS GENERAL IN THE AUDIT TO THE PROCESSES OF THE AREA OF COLLECTION AND PORTFOLIO OF THE CNEL EP, is carried out to verify compliance with the recommendations made by the Internal Audit to this public company as regards refers to compliance with the procedures and policies that regulate the activities of collection in the different Agencies that belong to the service area of ​​the CNEL EP, emphasizing the agencies of Ventanas, Vinces, Baba, Catarama; as well as the of consolidation and recovery of the portfolio; in the period between March 2013 to December 2016, where according to the audit report of the month of March 2017, indicates that the biggest problem detected in these Agencies is the lack of presentation by part of the collector of the daily reports of the partial or final cash closing which is generated by the commercial system; which is an established activity in the procedures internal